The determinants of bushmeat consumption in urban areas in Laos - Phoyduangsy Saysamone; Bounmy Inthakesone; Phonekeo Viraxay; Syphoxay Pakaiphone; CHANSAMONE Luanglath; Vannisa Thammachack (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
This study aims to examine the determinants of bushmeat consumption in urban areas in Laos. Men consume more bushmeat than women. Job, the government official was the major bushmeat consumer, but there was no proven by statistical approaches from this study we have done. The education of people who consume bushmeat has finished high school level. Ethnic, Lao Loum people have a negative impact on bushmeat consumption, but for Hmong or Lao Theung people, bushmeat is a long tradition of eating and being a major food source. In addition, believing in eating bushmeat can make people healthy is also valid.